2018
DOI: 10.3390/ma11020199
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation Induced Self-Healing Behavior of Al-Ag Alloy

Abstract: Self-healing alloys are promising materials that can decrease the consequences of accidents. To detect crack formation in a material is simple task that can be performed by e.g., sonic or ultrasound detection, but it is not always possible to immediately replace the damaged parts. In this situation, it is very advantageous to have the chance to heal the crack during operation, which can be done e.g., by annealing. In this paper, self-healing behavior was proven by TEM (Transmission electron microscope) observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Kevlar and Nomex represent notable examples of aramid fibers, prized for their flame-retardant properties, abrasion and impact resistance, and exceptional strength-to-weight ratios, making them indispensable for protective clothing, ballistic armour, and aerospace applications. Meanwhile, metallic reinforcements like Al, Ni, Ti, carbides (SiC, TiC, WC), borides (BN, TiB 2 , ZrB 2 , HfB 2 , B 4 C), oxides (SiO 2 , Al 2 O 3 , MgO, K 2 O, Y 2 O 3 ), carbon (CNTs), steel particulates, or fibers are frequently employed in metal matrix composites (MMCs) to enhance attributes like crack healing [81,85,86], thermal stability [87,88], solar absorbance [89,90], and mechanical properties including toughness, strength, wear, and corrosion resistance.…”
Section: Artificial Reinforcementsmentioning
confidence: 99%
“…Kevlar and Nomex represent notable examples of aramid fibers, prized for their flame-retardant properties, abrasion and impact resistance, and exceptional strength-to-weight ratios, making them indispensable for protective clothing, ballistic armour, and aerospace applications. Meanwhile, metallic reinforcements like Al, Ni, Ti, carbides (SiC, TiC, WC), borides (BN, TiB 2 , ZrB 2 , HfB 2 , B 4 C), oxides (SiO 2 , Al 2 O 3 , MgO, K 2 O, Y 2 O 3 ), carbon (CNTs), steel particulates, or fibers are frequently employed in metal matrix composites (MMCs) to enhance attributes like crack healing [81,85,86], thermal stability [87,88], solar absorbance [89,90], and mechanical properties including toughness, strength, wear, and corrosion resistance.…”
Section: Artificial Reinforcementsmentioning
confidence: 99%
“…In contrast, the middle phase among the three intermediates is identified as the δ phase. The intermediate phase on the Al-rich side aligns with an unknown phase, which we define as φ, unaccounted for in the binary Ag-Al phase diagrams [7,8,14,27].…”
Section: Microstructure and Compound Growth At The Interfacementioning
confidence: 99%
“…Hautakangas et al observed the autonomous healing of strain-induced defects in aluminum alloys via the precipitation of mobile Cu atoms at the defects with the help of positron annihilation spectroscopy [15]. Michalcova and coworkers discovered the crack-healing phenomenon caused by the precipitation of supersaturated Ag solutes in Al [16]. While fruitful research results have been gained in self-healing aluminum alloys, current research is mainly aimed at commonly used heatresistant aluminum alloy systems (AA2XXX series), and the selection of candidate elements for self-healing agents is limited to commonly used alloying elements, such as Cu.…”
Section: Site-specific Precipitationmentioning
confidence: 99%